2016
DOI: 10.1128/aac.00864-16
|View full text |Cite
|
Sign up to set email alerts
|

Rare Spontaneous Loss of Multiresistance Gene Carrying IncI/ST12 Plasmid in Escherichia coli in Pig Microbiota

Abstract: Resistance to extended-spectrum cephalosporins (ESCs) is a matter of considerable concern for public health. Here, we studied the spontaneous loss of an extended-spectrum beta-lactamase (ESBL)-encoding plasmid from a rifampin-resistant Escherichia coli isolate orally inoculated into pigs under controlled conditions. Fecal samples were collected and cultured on rifampin-supplemented medium, and the resistance of the E. coli isolates to ESCs was studied by phenotypic tests, PCR detection of plasmid genes, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Antimicrobial use is the principal driving force behind the current epidemic of antimicrobial resistance. However, research has shown that, once evolved, multidrug resistance plasmids can be maintained in the absence of selection (67). There is a dearth of fitness defects reported for resistance plasmids in the literature and the reasons why some of them are evolutionarily successful are not well understood (58,68).…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial use is the principal driving force behind the current epidemic of antimicrobial resistance. However, research has shown that, once evolved, multidrug resistance plasmids can be maintained in the absence of selection (67). There is a dearth of fitness defects reported for resistance plasmids in the literature and the reasons why some of them are evolutionarily successful are not well understood (58,68).…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial use is the principal driving force behind the current epidemic of antimicrobial resistance. However, research has shown that, once evolved, multidrug resistance plasmids can be maintained in the absence of selection 44 . There is a dearth of fitness defects reported for resistance plasmids in the literature and the reasons why some of them are evolutionarily successful are not well understood 41,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Animals and experimental design. As previously described in Mourand et al (10,12), the experiments were conducted in the ANSES, Ploufragan, France, animal facilities. The trials were conducted with 6-to 8-week-old specific pathogen-free and initially ESC-resistant E. colifree Large White piglets.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies using a series of experiments that included pigs inoculated with E. coli harboring bla CTX-M-1 -encoding IncI plasmid showed the maintenance of the plasmid in its E. coli host, in the pig’s gut. Moreover, the loss of the plasmid was a rare event in gut microbiota during these longitudinal studies of in vivo carriage in pigs (10). In these models, the transfer of the bla CTX-M-1 -encoding IncI plasmid between different E. coli strains occurred and underlines the dissemination capacity of the ESC resistance, independently of the exposure to antibiotic drugs (11, 12).…”
Section: Introductionmentioning
confidence: 99%